Liver Injury Secondary to Anti-TNF-Alpha Therapy in Inflammatory Bowel Disease: A Case Series and Review of the Literature - Ravish Parekh; Nirmal Kaur (Case Reports in Gastrointestinal Medicine)
Background. Biologic therapy to inhibit tumor necrosis factor-alpha (TNF-α) is an effective, safe treatment for patients with inflammatory bowel disease (IBD). All TNF-α inhibitors have been associated with liver toxicity, but many of these cases have been reported in patients receiving therapy for rheumatologic disease. Herein we report the first single-center case series of TNF-α antagonist related liver injury in patients with IBD. Methods. A retrospective case series was performed at the Henry Ford Inflammatory Bowel Diseases Center. IRB approval was obtained. Results. 2 patients were treated with infliximab, whereas the 3rd patient was treated with adalimumab for IBD. All 3 patients had negative viral markers, normal autoimmune serologies, and normal biliary imaging studies. Liver biopsy was performed in all 3 patients, and evidence of portal inflammation was seen. Liver enzymes normalized after discontinuation of therapy in all patients, and no long term effects have been observed. One patient was successfully transitioned from infliximab to adalimumab without relapse of either IBD or liver injury. Conclusion. Liver injury secondary to TNF-α antagonist is an underrecognized, important clinical entity with potentially serious consequences. The mechanism of drug-induced injury is idiosyncratic. Larger cohort studies are needed to establish risk factors and injury patterns related to hepatotoxicity in these patients.